(untitled) (Historia, 2021)
The Republican ultimatum to Great Britain, delivered on October 9,1899, had resulted in the war breaking out on October 11, and martial lawwas proclaimed in the two Republics. The initial Republican victories inNatal had been succeeded by retreats not only there but on all other fronts.Ladysmith and Mafeking were reliewd, Bloemfontein, the capital of thesister Republic, was occupied on March 13, 1900, and now Frederick Sleigh,Baron Roberts of Kandahar and Waterford, Commander-in-Chief of HerMajesty’s Forces in South Mrica, was marching from the Free State toPretoria with his forces at an average rate of nearly 17 miles per marchingday -a performance almost equal to the best recorded in military historyup to then -with the commanders on the other fronts trying to keep pacewith him.Although Lord Roberts’s advance was delayed by actions here andthere, the Vaal River was crossed somewhere near Viljoensdrift without anyserious opposition, and the British Army found itself within striking distanceof the Rand gold mines -one of the main causes of the war.By this time, General Louis Botha, unknown soldier at the outbreakof war, had succeeded General Piet Joubert and was, at this stage, actingCommandant-General of the Transvaal forces.Mainly due to his strong stand -and, let it not be forgotten, that ofPresident Kruger -the British found the gold mines undamaged when theyentered Johannesburg on May 31. The Republican Government, in spiteof strong demands and even personal attempts by some members to blowup the mines, had not been able to agree to any "scorched earth" policy.Meanwhile, the Volksraad on May 7, met for the last time in Pretoria.It was a sad occasion for the members -with many empty seats in theVolksraad Chamber draped in crepe, previously occupied by prominent mem-bers who by then had made the supreme sacrifice. Another empty seat wasthat of General Botha who was away at the front.